A comparative analysis of numerical and experimental optimization of CuSbS₂ absorber layer thickness for improved solar cell performance - Femi Emmanuel Ikuemonisan; Yusuf Olanrewaju Kayode; Opeyemi Balikisu Odubote (Next Materials)
Copper antimony sulfide (CuSbS₂) is an absorber material of interest for thin-film photovoltaics because of its earth abundance, suitable bandgap, and high absorption coefficient. However, its practical application is limited by low power conversion efficiency (PCE), often caused by insufficient control over the absorber layer thickness and an incomplete understanding of recombination mechanisms. The lack of integrated numerical and experimental studies has also slowed progress toward developing optimized device architectures. This study presents a comparative analysis of numerical simulations and experimental investigations to optimize the absorber layer thickness of CuSbS₂ solar cells for enhanced performance. SCAPS-1D simulations were conducted across a thickness range of ∼0.5–3.5 μm, incorporating critical parameters such as bulk defect density, carrier concentration, and interface recombination. Complementary experimental work involved synthesizing CuSbS₂ films via chemical bath deposition, followed by comprehensive material and device characterization. The effects of various buffer layers, including cadmium sulfide (CdS), indium (III) sulfide (In₂S₃), zinc sulfide (ZnS), and zinc selenide (ZnSe), on device performance were evaluated. The results show that optimizing the absorber thickness significantly improves device performance. The highest PCE recorded was 3.24 %, with a strong agreement between simulated and experimental data (correlation coefficient r = 0.84). Among the buffer layers studied, the CdS/CuSbS₂ configuration showed the best performance, with an open-circuit voltage (Voc) of 0.52 V and a fill factor (FF) of 58.7 %. This study addresses key challenges related to absorber layer optimization and the gap between simulation and experimental validation. It also provides a useful approach for controlling absorber thickness and understanding recombination losses. The results show that optimizing the absorber thickness significantly improves device performance.